Social Support on Burnout: Mindfulness as a Mediation Variable - Riani, Mareta; Syahrizal, Syahrizal (Human Resource Management Studies, 2023)
This study aims to examine: (1) the relationship between social support and burnout; (2) the relationship between social support and minfulness; (3) the relationship between mindfulness and burnout; and (4) the relationship between social support and burnout trough mindfulness. Method of this research is descriptive quantitative. Population of this research consists of 84 civil servants in Department of Marine and Fisheries of West Sumatra Province and all civil servants are made as the research sample. using a likert scale questionnaire to obtain data. Software called SmartPLS4 is utilized for the analytical methods. The analysis of the data in this study reveals that: (1) Social support has a significant and negative effect on burnout in civil servants at the marine and fisheries service of west sumatra province; and (2) Social support has a significant and positive effect on mindfulness in civil servants at marine and fisheries service of west sumatra province. (3) Mindfulness has a significant and negative effect on the levell of burnout in civil servants at the marine and fisheries service of west sumatra province. (4) Mindfulness can mediate the effect of social support on burnout in civil servants at the Marine and Fisheries Service of West Sumatra Province